О признании мировым научным сообществом результатов Института механики им. С.П. Тимошенко НАНУ - Гузь, А.Н. (Прикладная механика, 2015)
Стаття присвячена 100-річчю (1918 – 2018 рр.) Національної академії наук України (НАНУ) та Інституту механіки ім. С.П.Тимошенка НАНУ. Наводиться інформація про визнання світовим науковим співтовариством наукових результатів, які одержано вченими Інституту протягом часу його існування. Анонсується підготовка видання «Сучасні проблеми механіки» (в 3-х томах), присвяченого ювілею. This article is devoted to the forthcoming (in 2018) 100th anniversary of the National Academy of Sciences of Ukraine (NASU) and the S.P.Timoshenko Institute of Mechanics of NASU. Just on this account, the information on recognition of scientific results of the S.P.Timoshenko Institute of Mechanics by the world scientific community is presented. It is announced also the preparation of edition in three volumes «Modern Problems of Mechanics» that will be devoted to the forthcoming anniversary and will be based on the reviews of scientific results of scientists of the S.P.Timoshenko Institute of Mechanics published starting with 2011 in «Prikladnaya Mekhanika» in Russian and «International Applied Mechanics» in English.